(untitled) (Journal of educational development exploration, 2026)
Red financial culture constitutes a valuable spiritual asset formed by the Communist Party of China through its long-term financial and economic practices. It represents a distinctive manifestation of red culture within the field of finance and economics. Its educational value is primarily reflected in three aspects: it effectively fulfills the function of ideological guidance and aligns with the fundamental task of fostering virtue through education; it provides abundant indigenous practical teaching resources; and it helps cultivate a positive educational environment, enabling students to maintain firm ideological orientation amid diverse value systems. At present, however, the educational value of red financial culture has not been fully realized. It is therefore necessary to advance coordinated efforts at four levels: improving mechanisms for value transformation, strengthening mechanisms for disciplinary integration, reinforcing mechanisms for practical application, and establishing institutional support mechanisms. Through these measures, red financial culture can be deeply integrated into the talent cultivation system in finance and economics, thereby providing strong support for nurturing high-quality financial professionals in the new era who possess both patriotism and professional competence.